NATIONAL INTEGRATION AND ITS PROCESS IN INDONESIA - Mulyoto, - (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
National Integration covers the arrangement of culture, territory, power, value and behaviour. Basically, the integration process is a horizontal change for the view of local to national or even international people and vertical change of elite group establishment having power legitimation. Integration process in Indonesia experiences up and downs and it will not enable to satisfy any and all related elements. It is started by national revival to establish the independent country, to find the fit and proper governance, to build a country to be strong in the economy field and then find the independence in liberal democracy nature. National integration is processed in accordance with the history development.